Pengujian Usability Untuk Aplikasi Silsilah Keluarga Myheritage Dalam Memenuhi Kebutuhan Umat Islam Dengan Pendekatan Kuantitatif - Alfa Fidel Reyhan; Ismiarta Aknuranda; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Nasab is something that must be learned by Muslims and also nasab science related to other Islamic sciences such as inheritance and marriage. Therefore, we need an application that can record traces of family tree that can also help Muslims in meeting their nasab needs. MyHeritage is a family pedigree track record application that has been used by more than 1 million users worldwide. This research aims to find the level of usability of the MyHeritage application and also to find out whether this application meets the Muslim needs of nasab science. The usability testing method is used in this study by using a matrix of efficiency, effectiveness, error rate, and satisfaction to find the usability level. In this study also used SUS, SEQ, and closed-ended question questionnaires. The 31 participants were given a task scenario to do with a total of 19 tasks. Participants must also answer 19 questions in the SEQ questionnaire, each of which is done after completing each task. If all tasks and all SEQ questionnaires are completed, participants must fill in the closed-ended questionnaire and fill in the SUS questionnaire to measure satisfaction. MyHeritage application gets a value of 60.34% for the level of effectiveness and 60% for the level of efficiency. At the level of error rate, this application gets a value of 40.45% and a value of 47 on SUS which is low in the level of satisfaction. The MyHeritage application is felt to have fulfilled the Muslim needs for nasab science because all participants have argued that the kinship of the participants has been explained and 51.6% of the participants felt the need for their nasab was fulfilled